2014
DOI: 10.21236/ada602128
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Training on Performance

Abstract: This research effort was conducted to collect empirical evidence on the effectiveness of different training methods for acquiring and transferring complex cognitive skills. To accomplish this goal, we conducted a series of meta-analyses (and supplemental experiments) examining six training methods (training wheels, scaffolding, part-task training, increasing difficulty, learner control, and exploratory learning), as well as factors that moderate their effectiveness, such as task/skill type being trained (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…In summary, the present research was conducted as part of a broader four-year effort to develop evidence-based guidelines for the relative effectiveness of six different training methods for acquiring and transferring cognitive skills involved in complex task domains (see Plott et al, 2014). Several efforts were employed to develop these evidence-based guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the present research was conducted as part of a broader four-year effort to develop evidence-based guidelines for the relative effectiveness of six different training methods for acquiring and transferring cognitive skills involved in complex task domains (see Plott et al, 2014). Several efforts were employed to develop these evidence-based guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The present research was conducted as part of a broader four-year effort to develop evidence-based guidelines for the relative effectiveness of different training methods for learning and transferring cognitive skills involved in complex Army-relevant task domains (see Plott et al, 2014). The emphasis was on how to improve not only learning, but also how to improve training transfer -that is, the degree to which trainees are able to apply and use what they learned once back on-the-job or in a new context (see Kraiger, Ford, & Salas, 1993).…”
Section: Research Project Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, performance-based adaptive training does not always capture all the individual’s relevant aspects that impact learning [ 14 ]. In a meta-analysis of 22 studies, performance-adaptive training was found to have a significant benefit of 32% on learning rate and transfer effectiveness was improved compared with fixed or increasing difficulty training methods [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-controlled task difficulty is a simple method of adjusting the training complexity to the state of the trainee. It was found to have a positive effect on training under certain conditions [ 15 ]. In this type of training, the trainee has the option to self-manage the workload related to the process during training, which increases the efficiency of learning.…”
Section: Introductionmentioning
confidence: 99%